Angiotensin converting enzyme activity is positively associated with IL-17a levels in patients with schizophrenia. Issue 3 (30th October 2015) - Gadelha, Ary; Yonamine, Camila M.; Nering, Marcela; Rizzo, Lucas Bortolotto; Noto, Cristiano; Cogo-Moreira, Hugo; Teixeira, Antônio Lúcio; Bressan, Rodrigo; Maes, Michael; Brietzke, Elisa; Hayashi, Mirian A.F.
Abstract: Previous studies of our group showed increased plasmatic Angiotensin-I Converting Enzyme (ACE) activity in schizophrenia (SCZ) patients compared to healthy controls, which was also associated to poor cognitive functioning. The ACE main product angiotensin II (Ang-II) has pro-inflammatory properties. Activated immune-inflammatory responses in SCZ and their association with disease progression and cognitive impairments are also well-described. Therefore, we examined here the association of plasma ACE activity and inflammatory mediators in 33 SCZ patients and 92 healthy controls. Non-parametric correlations were used to investigate the association of the enzyme activity and the peripheral levels of immune inflammatory markers as interleukins, tumor necrosis factor (TNF-α), and interferon (IFN-γ). Although no significant correlations could be observed for ACE activity and measured cytokines levels in healthy controls, a significant positive correlation for ACE enzymatic activity and IL-17a levels was observed in SCZ patients. Correcting for gender did not change these results. Moreover, a significant association for ACE activity and IFN-γ levels was also observed. To our knowledge, this is the first study to show a significant association between higher ACE activity and the levels of cytokines, namely IL-17a and IFN-γ, in patients with SCZ. Highlights: ACE enzymatic levels are associated to inflammatory mediators in schizophrenia. No significant correlations were found for ACE activity and measured cytokines levels in healthy controls. A significant positive correlation for ACE enzymatic activity and IL-17a levels was observed in schizophrenia patients. Significant association for ACE activity and IFN-γ levels was also observed. Correcting for gender did not change these results.